Observer Agreement Regarding the Necessity of Retreatment of Previously Coiled Recurrent Cerebral Aneurysms - Daugherty, W.P. (AJNR Am J Neuroradiol, 2011)
BACKGROUND AND PURPOSE: The decision regarding whether or not to retreat a previously treated aneurysm not only directly impacts patient care but also serves as a primary outcome measure in numerous, leading randomized controlled trials of modified coils. Our aim was to determine the degree of interobserver variability regarding the need and type of treatment for recurrent aneurysms following coil embolization. MATERIALS AND METHODS: Twenty-seven previously treated recurrent aneurysms were identified. Five independent readers rated each aneurysm on a 5-point scale: 1, definitely do not retreat; 2, probably do not retreat; 3, unsure; 4, probably retreat; and 5, definitely retreat. The readers noted, in grades 2–5, the type of retreatment preferred, including simple coiling, balloon- or stent-assist coiling, or surgical clipping. Intraobserver agreement κ was calculated. Retreatment recommendations were evaluated between observers by using a Wilcoxon signed rank comparison. Descriptive statistics were performed for categoric treatment-type comparisons. RESULTS: At least 2- or 3-point differences between 2 readers were present in 17 (63%) and 11 (41%) of 27 cases, respectively. The median κ was 0.27 (range, 0.04–0.43), which indicates fair agreement. Differences between readers varied, with readers 4 and 5 more often recommending retreatment compared with reviewers 1–3 (P < .05). Wide variation was noted in treatment approach, with recommendations for surgical clipping ranging from 2 (7%) to 18 (67%) of 27 cases between readers 1 and 5. CONCLUSIONS: The current study demonstrates substantial variability among observers not only in whether to retreat a recurrent aneurysm but also how to treat it. These findings suggest that patient management varies widely across treating physicians and also calls into question the use of “retreatment” as an objective end point in clinical trials.